The agenda of the French news agency AFP in dealing with the press image of the peaceful resistance The Great Return Marches as a model "an analytical study" - Wafi, Amin Mansour (ALBAHITH ALALAMI, 2020)
The study aimed to identify the treatment of the press image of the Great Return Marches in the French international news agency AFP by knowing the most important issues, their direction and the degree of interest in them. The study belongs to the descriptive research, and used the survey method, within the context of the content analysis method, and the researcher relied on the content analysis form tool and the interview tool to collect data. The study population is represented in the photos published by the French News Agency about the Great Return Marches during the period (end of March / 2018 until the end of November / 2019. The researcher chose an intentional sample using the Complete Census method. The study material represented all the photos related to the Great Return Marches. The researcher relied on the agenda theory of "priority order''. Among the most important results: The study showed photos of the political issues of the Great Return Marches by (81.7%); The sources of the press photo came from the agency’s photographers themselves (96.7%); The negative trend of the press image Great Return March came (91.2%); Among its most important recommendations: The French agency AFP should pay attention to the press pictures with a positive trend; increasing interest towards the different types of press photos according to its content and focusing on the personal image.